Oral and Maxillofacial Surgery for the Clinician - Bonanthaya, Krishnamurthy; Panneerselvam, Elavenil; Manuel, Suvy.; Kumar, Vinay V.; Rai, Anshul; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2021)
This book is an open access book with CC BY 4.0 license. This comprehensive open access textbook provides a comprehensive coverage of principles and practice of oral and maxillofacial surgery. With a range of topics starting from routine dentoalveolar surgery to advanced and complex surgical procedures, this volume is a meaningful combination of text and illustrations including clinical photos, radiographs, and videos. It provides guidance on evidence-based practices in context to existing protocols, guidelines and recommendations to help readers deal with most clinical scenarios in their daily surgical work. This multidisciplinary textbook is meant for postgraduate trainees, young practicing oral surgeons and experienced clinicians, as well as those preparing for university and board certification exams. It also aids in decision-making, the implementation of treatment plans and the management of complications that may arise. This book is an initiative of Association of Oral and Maxillofacial Surgeons of India (AOMSI) to its commitment to academic medicine. As part of this commitment, this textbook is in open access to help ensure widest possible dissemination to readers across the world.
Oral and Maxillofacial Surgery in India. How did we get here and where are we going? -- Pre-Operative Evaluation & Investigations -- Management of Medically Compromised Patients -- Management of Medical Emergencies -- Local Anaesthesia -- Oral and Maxillofacial Surgery -- Ambulatory Anesthesia Model and Training -- Anesthesia for OMFS -- Radiology for the Oral and Maxillofacial Surgeon: The Essentials -- Sterilisation and Operating Room Protocols -- Pharmacotherapy in OMFS -- Wound closure and Suturing Methods -- Management of the Post operative OMFS Patient -- Principles and Techniques of Exodontia -- Management of the Impacted tooth: A : Third Moalr impactions -- Canine Impactions -- Endodontic surgery -- Pre prosthetic Surgery -- Basic Implantology -- Bone Augmentation Procedures in Implantology -- Odontogenic Infections - General Principles -- Space Infections -- Osteomyelitis /ORN/ MRONJ -- Maxillary Sinusitis -- Management of Oro Antral Communications & Fistulae -- Trigeminal Nerve Injuries.-Trigeminal Neuralgia -- Cysts of the OMF region -- Odontogenic Tumours -- Reactive Lesions of the Oro Maxillofacial Region -- Fibro Osseous Lesions -- Vascular Anomalies of the Oro Maxillofacial Region -- Non-Surgical Modalities of Facial Rejuvenation & Aesthetics -- Botox & Fillers -- Hair Transplant -- Ear Reconstruction -- Management of Scars -- Face Lifts -- Rhinoplasty -- Lasers in OMFS -- Peizo Surgery in OMFS -- Role of Computer-assisted Navigation Surgery in Oral and Maxillofacial Surgery -- Human Factors and Reducing Medical Error.-Setting up an OMFS Facility -- Legal Issues in OMFS -- Research & Publication -- Salivary Gland Disorders -- Salivary Gland Tumours -- Obstructive Salivary Gland disease and Sialendoscopy -- Primary Assessment & Care of the Maxillofacial Trauma Patient -- Soft Tissue Injuries -- Dento Alveolar Fractures & Wiring techniques -- Plating Systems & Principles of ORIF -- Mandibular Fractures -- Condylar Fractures of the Mandible -- Intraoral Endoscopic Approach for Condylar Fractures -- Maxillary Fractures -- Zygomatic Complex Fractures -- Orbital Fractures -- Frontal & NOE Fractures -- Gunshot Injuries -- Panfacial Trauma -- Residual Deformities -- MPDS -- Internal Derangements of TMJ -- TMJ Ankylosis -- Dislocation/ Subluxation -- Alloplastic Reconstruction -- Diagnosis & Planning -- Facial Asymmetry -- Mandibular Procedures -- Maxillary Procedures -- SFOA -- OSAS -- Complications in Orthognathic Surgery -- Cleft Lip -- Cleft Palate -- Alveolar Bone Grafting -- Cleft Maxillary Hypolplasia -- Cleft Rhinoplasty -- Transport Distraction Osteogenesis -- Distraction Osteogenesis: Craniofacial , Pediatric -- Rare Facial Clefts -- Hemifacial Microsomia / Treacher Collins -- Craniosynostosis -- Pre malignant Lesions and Conditions -- Carcinoma Diagnosis & Treatment Planning -- Principles of Surgical Management of Oral Cancer -- Sarcoma -- Adjunctive Therapy -- Access Surgeries/Osteotomies -- Soft Tissue Reconstruction -- Hard Tissue Reconstruction.
Keywords: Mouth -- Surgery; Oral and Maxillofacial Surgery